Perawatan Luka Diabetes Mellitus Menggunakan Teknik Modern Dressing - Alberikus Dimantika; Sugiyarto Sugiyarto; Yuyun Setyorini (Poltekkes Kemenkes Surakarta, 2020)
Background: The most common complication in patients with diabetes mellitus tippe 2 (DM) is diabetic ulcers, where the tissue deformity occurs either partially (Partial Thickness) or completely (Full Thickness). If not handled properly and appropriately, ulcers can become infected. Where leg ulcers, infection, neuroarthropathy and peripheral artery disease are the causes of gangrene and lower limb amputations. The aim of this study is to determine the effectiveness of wound healing in the treatment of diabetes mellitus wounds using modern dressing techniques. Methods: the literature review (LR) method uses meta-analysis where the data used is a database of searches using MEDLINE (PubMed), Google Scholar, Science Direct, Surgery Science and Sci-Hub. Reports published from 2010-2020 that focused on modern wound care dressings for wound healing of type 2 diabetes mellitus were identified. Results: Based on the analysis of the journal, there are nursing implications that have been compared from 10 journals, it was found that the treatment of type two diabetes mellitus wounds using modern dressing techniques is more effective in wound healing, by accelerating granulation and healing of the various types of dressings used, each of which has advantages. in terms of wound healing type 2 diabetes mellitus. Conclusion: The use of modern dressing techniques is effective in wound healing in the treatment of type 2 diabetes mellitus wounds. Researchers suggest that they be able to conduct research related to modern wound care dressings such as the use of alginate dressings, foam dressings, hydrogel dressings, moisture dressings, silver dressings, hydrophilic polyurethane foam dressings, acellular matrix dressings, and others related to wound care using modern dressing techniques. . Further research needs to be done by paying attention to the latest evidence-based practice journals to enrich knowledge about wound care with modern dressing techniques for diabetes mellitus wounds.